MODELS FOR THE LORENZ SYSTEM - Zlatanovska, Biljana; Dimovski, Dončo (Matematichki Bilten, 2018)
Using the systems of difference equations from [1] and [2], as approximation for the solutions of the Lorenz system of differential equations, we obtain two new systems of difference and differential equations as models for the Lorenz system. By computer simulations as in [3] and [4] we give examples, where locally the solutions of these new systems, approximate the solutions of the Lorenz system.